Online Learning at SD Muhammadiiyah 1 Krian during the Covid-19 Pandemic - Vindiyati Puspitasari; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The development of education today is influenced by the rapid progress of information and communication technology. One of the information technologies that play a role in the world of education in online learning. Online learning functions as a link between edeucators and students with an internet network that can be accesed anytime and anywhere. The online media used by the research subjects were various (WhatsApp, Google Classroom, Website). In online learning, teachers have the challenge of creating creative, smart (smart teaching), ), and fun learning (joyful learning). A teacher must pay attention to the context of students, supporting facilities and infrastructure, as well as the demands of the curriculum so that it can create effective and enjoyable learning. The purpose of this study was to determine the learning strategies at SD Muhammadiiyah 1 Krian online. The method collected in data collection was a question and answer question to the resource person, namely one of the teachers at SD Muhammadiiyah 1 Krian. The methods used during online learning in the midst of this pandemic are numerous.